2009
DOI: 10.7863/jum.2009.28.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic Measurements of the Thymus in Male and Female Fetuses

Abstract: These results suggest that fetal sex does not affect the size of the thymus and, together with previous reports, support the hypothesis that a quantitative reduction in fetal thymus size could serve as an indirect marker of abnormal thymopoiesis and congenital thymic insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 28 publications
2
22
0
4
Order By: Relevance
“…As described in previous studies, this gland develops in a linear pattern during fetal life, 2 , 11 – 16 which was also confirmed in our study (Figure 3). No differences were found between male and female fetuses or between singleton and twin bichorionic and monochorionic pregnancies, and these findings were consistent with previous data 16 , 21 , 22 . The thymic transverse diameter also shows a higher variation throughout pregnancy than the anteroposterior diameter, which has been described with other techniques as well and may be related to the anatomy of the mediastinum 2 , 12 , 16 , 21 , 23 …”
Section: Discussionsupporting
confidence: 91%
“…As described in previous studies, this gland develops in a linear pattern during fetal life, 2 , 11 – 16 which was also confirmed in our study (Figure 3). No differences were found between male and female fetuses or between singleton and twin bichorionic and monochorionic pregnancies, and these findings were consistent with previous data 16 , 21 , 22 . The thymic transverse diameter also shows a higher variation throughout pregnancy than the anteroposterior diameter, which has been described with other techniques as well and may be related to the anatomy of the mediastinum 2 , 12 , 16 , 21 , 23 …”
Section: Discussionsupporting
confidence: 91%
“…Fetal thymic measurements were obtained in duplicate by the same observer, allowing for a 5‐min interval between examinations. Intra‐ and interobserver reproducibility of fetal thymic measurements at our institution have been previously reported9, 23. Clinical information was retrieved from maternal and neonatal medical records by one of the investigators (P.P.…”
Section: Methodsmentioning
confidence: 99%
“…Measurements of the size of the thymus can also be used to detect ‘thymic involution’ due to apoptosis of cortical thymocytes4 after the activation of the hypothalamic–pituitary–adrenal axis in response to acute respiratory distress syndrome, trauma, sepsis, malnutrition, physical stress or graft versus host disease5–7. Several authors have already reported on the normal development of the fetal thymus in singleton pregnancies2, 8–10. Moreover, during the prenatal period, the size of the thymus has been correlated with T‐cell output11–14 and the numbers of circulating CD41 and CD45RA1 naïve T‐cells15, opening up the possibility of making fetal thymic measurements a promising non‐invasive screening tool for the prenatal diagnosis of functional thymic insufficiency in response to activation of the stress pathway.…”
Section: Introductionmentioning
confidence: 99%
“…11,13,[27][28][29] Consequently, methods have been developed to visualize and measure the thymus using sonography, and the feasibility of these methods is similar (Table 6). [30][31][32][33][34] However, the need to include color Doppler imaging to visualize the internal mammary arteries can diminish the accuracy of visualization, especially in adverse fetal positions.…”
Section: View Viii: the Thy-boxmentioning
confidence: 99%